Biochemical characterization and variability in garden pea (Pisum sativum var. hortense) under cool hilly weather conditions - HEDAU, NIRMAL KUMAR; PAL, RAMESH SINGH; SOOD, SALEJ; VASUDEO, CHAUDHARI GANESH; KANT, LAKSHMI; PATTANAYAK, ARUNAVA (The Indian Journal of Agricultural Sciences, 2018)
Malnourishment is widespread and severe problems in most of the developing countries, and nutritionally rich food can address this issue efficiently by introducing nutritionally rich cultivars for cultivation. In this endeavor, 33 genotypes (30 agronomically superior advance lines and three cultivars) were analyzed for nutritional and essential agromorphological attributes. This set of materials has shown wide significant variations for most of the nutritional attributes indicating significant levels of genetic diversity. Antioxidant metabolites (total carotenoids and total polyphenols) and total chlorophyll were positively correlated with each other. First, four principal components explained 70.47% of the total variation. Best-performing lines were marked for important nutritional and agro-morphological attributes and may be tested in the multi-location trial to be released as new nutritionally rich cultivars for on-farm production.Alternatively, these could also be of instant significance as a donor in the future breeding program.